Hubungan antara Hukum Upacara Hukum Taurat Tuhan dan Kasih Karunia - Joshua Diets; Juwinner Dedy Kasingku (CV Putra Publisher, 2023)
The purpose of this study is to explain that law is the foundation that keeps humans on the right path. With the law, humans can live in peace and order. With the existence of law, humans can also see the true character of God, which is love. Grace is a gift God gives to humans that is not worthy for humans to receive. Jesus Christ is proof of that grace. The purpose of this study is to explain to the readers the differences between the two laws, namely the ceremonial law and the Torah law, because many people think that the law is no longer valid. This study uses a qualitative research method with a literature study approach where researchers use various literature to compare one quote with another to support this research. The results of this study state that God has never abolished His commands forever. He is a God who is consistent and never changes. If we see one verse as if it contradicts another, we haven't studied the Bible seriously. We should not just conclude from one verse. We have to compare one poem with another poem. Let the Bible explain itself.